Early B cell transcriptomic markers of measles-specific humoral immunity following a 3rd dose of MMR vaccine - Haralambieva, Iana H.; Chen, Jun; Quach, Huy Quang; Ratishvili, Tamar; Warner, Nathaniel D.; Ovsyannikova, Inna G.; Poland, Gregory A.; Kennedy, Richard B. (Frontiers in Immunology, 2024)
B cell transcriptomic signatures hold promise for the early prediction of vaccine-induced humoral immunity and vaccine protective efficacy. We performed a longitudinal study in 232 healthy adult participants before/after a 3rd dose of MMR (MMR3) vaccine. We assessed baseline and early transcriptional patterns in purified B cells and their association with measles-specific humoral immunity after MMR vaccination using two analytical methods ("per gene" linear models and joint analysis). Our study identified distinct early transcriptional signatures/genes following MMR3 that were associated with measles-specific neutralizing antibody titer and/or binding antibody titer. The most significant genes included: the interleukin 20 receptor subunit beta/IL20RB gene (a subunit receptor for IL-24, a cytokine involved in the germinal center B cell maturation/response); the phorbol-12-myristate-13-acetateinduced protein 1/PMAIP1, the brain expressed X-linked 2/BEX2 gene and the B cell Fas apoptotic inhibitory molecule/FAIM, involved in the selection of high-affinity B cell clones and apoptosis/regulation of apoptosis; as well as IL16 (encoding the B lymphocyte-derived IL-16 ligand of CD4), involved in the crosstalk between B cells, dendritic cells and helper T cells. Significantly enriched pathways included B cell signaling, apoptosis/regulation of apoptosis, metabolic pathways, cell cycle-related pathways, and pathways associated with viral infections, among others. In conclusion, our study identified genes/pathways linked to antigen-induced B cell proliferation, differentiation, apoptosis, and clonal selection, that are associated with, and impact measles virus-specific humoral immunity after MMR vaccination.